Library in ICTA Days - (:unkn) unknown (My University, 2009)
A black and white photograph of the Library of the Imperial College of Tropical Agriculture in 1922. The Library was held in the Main Administration Building
Black and white photograph.
Keywords: ICTA; Imperial College of Tropical Agriculture; Library; 1922; Administration building